(untitled) (Archive of Conferences, 2022)
Uzbek linguistics subject is one of the historical subjects. Its roots turn on the works of Mahmud Koshgariy, Mahmud Zamakhshariy, Avitsienna, Abu Rayhon Beruniy, Abu Nasr Forobiy, Alisher Navoiy, Sulaymon Bukhoriy. In the golden age of Uzbek linguistics in XX and XXI centuries, the role of scientist women is incomparable. Nearly 200 people defended candidate, 50 people defended doctoral theses on this subject, half of them done by scientist women. This article discusses about the role of scientist women in the development of the subject Uzbek linguistics.